'Don't ever mix God with sports': Christian religion in athletes' stories of life transitions. Issue 4 (2nd April 2020) - Ronkainen, Noora J.; Ryba, Tatiana V.; Tod, David
Abstract: Sport psychology researchers have increasingly recognized the need to adopt a holistic perspective when seeking to understand athletes' adaptation to life transitions. The present study sought to understand how religion influences athletes' journeys in sport and experiences of life transitions. Two Christian elite athletes participated in life story interviews which we analyzed via narrative analysis. Although the participants narratively separated religious belief from sport, religion, as a source of basic world assumptions and values, provided a broader framework of meaning and continuity in their sport lives. Yet, both stories involved a growing distance to institutional religious practices and movement towards individualized religiosity as they traversed cultural and developmental transitions. For applied practitioners, it is important to be aware of the unique ways in which religion influences the sport life and to recognize personal and cultural attitudes that will shape their applied work with religious athletes.